Voltage stability analysis in a subtransmission system, using qv-pv curves and modal analysis - Peña, Rogger (2021)
Voltage instability in a subtransmission electrical system in the Province of Manabí can occur in different ways such as: increased load, maximum machine performance operability, very remote generation points, very high inductive reactive powers, among others. All this generates problems in the sub-transmission of electrical power in the voltages and angles of the nodes of the system, by obtaining the PV curves it was identified that the Chone bar of 69 kV is the most critical and the QV the Manta bar of 69 kV under normal grid conditions using DigSilent software. With the increased load of 0.1 Mvar, the demand projections will be made using the reduced Jacobian matrix to obtain the participation factors, where the most critical of the branches is the Quevedo substation that has 0.8986 and the Daule-Peripa generation that arrives to have a value of 1, where all these operations were performed in Matlab. The need for this study analysis is of great importance, since with these projection values ​​a voltage instability will be created and the network would collapse.